Updating the parameters of “calculated runners” used in the design of gravity humps - S. A. Bessonenko; A. A. Gunbin; A. A. Klimov (Вестник Научно-исследовательского института железнодорожного транспорта, 2024)
Introduction. The design of the longitudinal side of the gravity humps provides for the implementation of structural and technological calculations, which simulate the rolling of the cut of single cars with established characteristics —“calculated runners”. The fleet of cars has been significantly updated, the share of cars with an axle load of 25 t has increased, and the innovative cars models with an axle load of 27 t has been constructed since the development of the gravity humps design standards. The object of research in this work is the numerical characteristics of the main specific resistance to movement of cars when rolling down a gravity hump. The subject of the study are the values of the main specific resistance to movement of “calculated runners” for modern car fleet circulation on the Russian railway network. The purpose of the study is to update the parameters of the main specific resistance to movement of “calculated runners” used in the design of a gravity hump.Materials and methods. The researchers made in-field observations of single cars rolling down a real gravity hump. The observations were made on a straight track section without braking within the measurement area in summer. The statistical analysis of single cars rolling on the same gravity hump in summer involved a computer vision system developed by the Rostov Branch of the Research and Design Institute for Information Technology, Signalling and Telecomminucations in Railway Transportation.Results. The authors obtained new values of the main specific resistance to movement for the established types of “calculated runners”, which have significantly decreased compared to existing standards. The use of new characteristics of “calculated runners” would improve the quality of gravity humps calculations in the development of design solutions for height, longitudinal side and technical equipment of gravity humps.Discussion and conclusion. The obtained results showed the need to adjust the rules and design standards of shunting facilities in terms of determining the values of the main specific resistance to movement for the established types of “calculated runners”. In order to introduce new values of the main specific resistance to movement into regulatory documents, it is advisable to continue research in order to expand the sample size and clarify the obtained results. At the same time, similar studies should be performed at different marshalling yards of the network located in different climatic zones.